Comparison of CRISPR–Cas Immune Systems in Healthcare-Related Pathogens - Mortensen, Kate; Lam, Tony J.; Ye, Yuzhen (Frontiers in Microbiology, 2021)
The ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) and Clostridium difficile have been identified as the leading global cause of multidrug-resistant bacterial infections in hospitals. CRISPR-Cas systems are bacterial immune systems, empowering the bacteria with defense against invasive mobile genetic elements that may carry the antimicrobial resistance (AMR) genes , among others. On the other hand, the CRISPR-Cas systems are themselves mobile. In this study, we annotated and compared the CRISPR-Cas systems in these pathogens, utilizing their publicly available large numbers of sequenced genomes (e.g., there are more than 12 thousands of S. aureus genomes). The presence of CRISPR-Cas systems showed a very broad spectrum in these pathogens: S. aureus has the least tendency of obtaining the CRISPR-Cas systems with only 0.55% of its isolates containing CRISPR-Cas systems, whereas isolates of C. difficile we analyzed have CRISPR-Cas systems each having multiple CRISPRs. Statistical tests show that CRISPR-Cas containing isolates tend to have more AMRs for four of the pathogens (A. baumannii, E. faecium, P. aeruginosa, and S. aureus). We made available all the annotated CRISPR-Cas systems in these pathogens with visualization at a website (https://omics.informatics.indiana.edu/CRISPRone/pathogen), which we believe will be an important resource for studying the pathogens and their arms-race with invaders mediated through the CRISPR-Cas systems, and for developing potential clinical applications of the CRISPR-Cas systems for battles against the antibiotic resistant pathogens.